Influence of Br.Sp-1, Br.Sp-2 Strains of Nodule Bacteria and the Biopreparation "Bioquvvat" on the Ability of the "Barqaror" Mung Bean Variety to Form Nodules - Murodullo AMIROV; Yuldash SAIMNAZAROV; Zoir SHOKIROV; Anvar ABDULLAEV (American Journal of Biology and Natural Sciences, 2025)
In the experiment, the influence of strains of nodule bacteria Br.sp-1, Br.sp-2 and the biopreparation "Bioquvvat" on the formation of nodules of the "Barqaror" mung bean variety was studied. During the experiment, the formation of tubers varied in each variant depending on the type of biopreparation and the plant variety. The highest indicator for the "Barqaror" variety was observed in the 2nd variant of the experiment when sowing mung bean seeds inoculated with the biopreparation "Bioquvvat." At the same time, an average of 66.2 tubers formed on each plant. The lowest indicator was observed in the control variant - 33.9 tubers were formed.